The Influence Of Technological Capability, Social Capital, and Entrepreneurial Orientation On Firm Performance Through Absorptive Capacity In Food and Beverage Packaging Industry Companies - Darmawan, Arif; Hadi , Hamdy; Sri Wahyudi, Agustinus (Journal of Comprehensive Science, 2023)
The purpose of this study is to present a model that illustrates the general influence of technological capability, social capital, entrepreneurial orientation on firm performance through absorptive capacity in the food and beverage packaging industry in Indonesia. The model proposed in this study was tested with a structural equation model. This study processed data from 168 respondents of manager-level employees to the company owner level in the food and beverage packaging industry. This study found that technological capability, social capital and absorptive capacity have a positive and significant effect on firm performance. Meanwhile, entrepreneurial orientation has a positive but not significant effect on firm performance. This study found that technological capability, social capital and absorptive capacity have a positive and significant effect on firm performance. Meanwhile, entrepreneurial orientation has a positive but not significant effect on firm performance. Absorptive capacity mediates the relationship between technological capability and social capital to firm performance and absorptive capacity fully mediates the relationship between entrepreneurial orientation and firm performance. This research model only limits the factors that affect company performance to four main variables, namely technological capability, social capital, entrepreneurial orientation and absorptive capacity. Further research is suggested to use samples in other industries and add other variables such as uncertainty or uncertainty of environmental conditions as moderation variables. The practical implications of this research are that companies need to do three things if they want to get the benefits of entrepreneurial orientation and absorptive capacity to improve firm performance. Further research is suggested to use samples in other industries and add other variables such as uncertainty or uncertainty of environmental conditions as moderation variables. The practical implications of this research are that companies need to do three things if they want to get the benefits of entrepreneurial orientation and absorptive capacity to improve firm performance. The new knowledge gained is very helpful for companies to determine strategies, levels of innovation, proactiveness and high-risk decisions, especially when there is uncertainty in the industrial environment. This study presents the mediating function of absorptive capability tested simultaneously with the variables technological capability, social capital, entrepreneurial orientation is something new from this study compared to previous studies. The findings in this study also provide an additional contradictory list of previous studies on the relationship between entrepreneurial orientation and firm performance.